2021
DOI: 10.3390/nu13061974
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Protein Components of Cow’s Milk against Certain Tumor Entities

Abstract: Milk and dairy products, especially from cow’s milk, play a major role in the daily human diet. It is therefore hardly surprising that the subject of milk is being extensively researched and that many effects of individual milk components have been characterized as a result. With the wealth of results available today, the influence of milk on the development of various types of cancer and, in particular, its often protective effects have been shown both in vitro and in vivo and in the evaluation of large-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 129 publications
0
9
0
Order By: Relevance
“…When studies regarding the effect of purified/synthetized BCM peptides were reviewed, it was reported that they may improve the proliferation of lymphocytes and the generation of antibodies, while negatively regulate the proliferation of leukemia cells ( 16 , 21 ). The anti-proliferative effect of BCM-7 has also been reported in a series of studies on prostatic cancer cells, breast cancer T47D cells and HL-60 promyeloic leukemia cells ( 23 ).…”
Section: Methodsmentioning
confidence: 63%
“…When studies regarding the effect of purified/synthetized BCM peptides were reviewed, it was reported that they may improve the proliferation of lymphocytes and the generation of antibodies, while negatively regulate the proliferation of leukemia cells ( 16 , 21 ). The anti-proliferative effect of BCM-7 has also been reported in a series of studies on prostatic cancer cells, breast cancer T47D cells and HL-60 promyeloic leukemia cells ( 23 ).…”
Section: Methodsmentioning
confidence: 63%
“…It was not until the 2010s that an increase occurred, and reviews of the implications of β-casein variants for human health were published [ 3 , 18 , 19 , 34 ]. During the years 2020 and 2021, the maximum number of publications on this topic was reached [ 14 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the casein and whey protein fractions of milk showed antitumor effects in an animal model as well as in vitro antiproliferative activity [36]. In addition, Elzoghby et al [37] reported that casein nanoparticles can be used to encapsulate the hydrophobic anticancer drug, flutamide, to control the drug release, improve its anti-tumor activity, and decrease its hepatotoxicity.…”
Section: Anticancer Activity Of Mp and Mpmcmentioning
confidence: 99%